Microwave-Assisted Protocol for Green Functionalization of Thiophenes With a Pd/β-Cyclodextrin Cross-Linked Nanocatalyst - Tabasso, Silvia; Calcio Gaudino, Emanuela; Acciardo, Elisa; Manzoli, Maela; Bonelli, Barbara; Cravotto, Giancarlo (Frontiers in Chemistry, 2020)
Microwaves (MW) are often the most efficient, in terms of heat exchange and conversion rate, of all the energy sources used to promote chemical reactions thanks to fast volumetric dielectric heating, and metal-catalysed synthetic reactions under heterogeneous conditions are an eloquent example. We herein report a MW-assisted green protocol for the C-H arylation of thiophenes with substituted aryl halides. This sustainable protocol is catalysed by Pd nanoparticles embedded in cross-linked β-cyclodextrin, and is carried out in γ-valerolactone (GVL). In view of the excellent results achieved with activated substrates, the one-pot synthesis of a 4(3H)-quinazolinone derivative has been accomplished. A pressure-resistant MW reactor, equipped with multiple gas inlets, was used for sequential (i) C-H arylation, (ii) reduction and (iii) carbonylation in the presence of the same catalyst, but under different gas atmospheres. The robust heterogeneous Pd catalyst showed limited metal leaching in GVL, making this an efficient MW-assisted process with high atom economy.